2017
DOI: 10.1038/srep45975
|View full text |Cite
|
Sign up to set email alerts
|

Running exercise strengthens the intervertebral disc

Abstract: There is currently no evidence that the intervertebral discs (IVDs) can respond positively to exercise in humans. Some authors have argued that IVD metabolism in humans is too slow to respond anabolically to exercise within the human lifespan. Here we show that chronic running exercise in men and women is associated with better IVD composition (hydration and proteoglycan content) and with IVD hypertrophy. Via quantitative assessment of physical activity we further find that accelerations at fast walking and sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
83
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(88 citation statements)
references
References 28 publications
3
83
2
Order By: Relevance
“…L4-L5 and L5-S1) have been found to be the most common sites for disc degeneration [22] and disc herniation [23]. In contrast to our findings, Belavý et al [11] found that there was no difference in Pfirrmann grades between participants who were not regularly involved in sport compared to runners. Their population was an average of 20yr younger, and morphological changes due to age and activity may have not yet manifested themselves (at least not on MR images).…”
Section: Runners (N = 9)contrasting
confidence: 99%
See 4 more Smart Citations
“…L4-L5 and L5-S1) have been found to be the most common sites for disc degeneration [22] and disc herniation [23]. In contrast to our findings, Belavý et al [11] found that there was no difference in Pfirrmann grades between participants who were not regularly involved in sport compared to runners. Their population was an average of 20yr younger, and morphological changes due to age and activity may have not yet manifested themselves (at least not on MR images).…”
Section: Runners (N = 9)contrasting
confidence: 99%
“…T2-time and ADC) did not differ between groups, despite differences in Pfirrmann grade. Previously, Belavý et al [11] found significantly longer T2-times in runners compared to non-athletic individuals. The discrepancy between our findings may be explained by the age difference of our participants.…”
Section: Runners (N = 9) Control (N = 8) P-valuementioning
confidence: 91%
See 3 more Smart Citations